The Irrawaddy River Jet in the Andaman Sea During the Summer Monsoon - Pargaonkar, Shrikant M.; Vinayachandran, P. N. (Frontiers in Marine Science, 2022)
The Irrawaddy (IR) is the largest river discharging into the Andaman Sea and plays an important role in the salinity distribution and the mixed layer physics of the Andaman Sea. This study presents the first report of the IR plume pathways in the Andaman Sea during the summer monsoon and the mechanisms behind them. An ocean circulation model is employed to conduct idealized experiments in which the freshwater forcing, due to rivers other than IR as well as precipitation, are ignored. Our simulations reveal that, during the summer monsoon, the discharge from Irrawaddy spreads as a freshwater jet oriented towards southeast and accumulates over the shelf at the eastern coast of the Andaman Sea. Climatology of Chlorophyll-a concentration measured by satellite and surface currents from global ocean model reanalysis indicates the presence of the Irrawaddy freshwater jet during the summer monsoon. The evolution of surface salinity and currents along the jet suggests that the IR freshwater traps momentum imparted by winds. The momentum balance in the Irrawaddy jet is between Coriolis and wind friction term, indicating that the freshwater jet is completely driven by winds during the summer monsoon. Surface distribution of wind friction term also shows that the northwest-southeast orientation of the Irrawaddy jet is due to the southwesterly orientation of the summer monsoon winds. Further experiments with three different wind forcing scenarios (no winds, winds over the equator only, and winds over the Bay of Bengal only) reveal that the flow of Irrawaddy jet during the summer monsoon is completely controlled by the local winds.